PENGARUH PAJAK PENGHASILAN 25 TERHADAP DIVIDEN PAYOUT RATIO PADA PT.TELKOM RATIO (PERSERO) Tbk - Andi Rustam; Amran Amran (Jurnal Riset Perpajakan: Amnesty, 2019)
Problem in this research is how income tax effect of article 25 against the dividend of payout ratio at PT. Telkom (Persero) Tbk. This method of research is a quantitative study with an ex-post facto approach, for which the free variable is income tax of article 25 measured by rupiah (Rp) and its variable is the dividend payout ratio Measured by stock ratio. The results of the regression equation then acquired Y =-90.429 + 4, 413X which means any addition of free variables (income tax article 25) as much as 1%. Based on the results of the test – T obtained a T-count value of = 2.155 while the T-table value in the Significant level of 95% (α = 0.05) and DK = N-2 (5-2) = 3, obtained 3.182 value. This indicates that T – count smaller than the T-table 1.897 ˃ 3.182. In addition to the probability of income tax (X) of 0.120 ˂ α = 0.05, the hypothesis of income tax of article 25 does not affect dividends PT. Telkom